Implementasi Model Pembelajaran Terpadu Nested pada Materi IPAS Kelas 4 - Luma’ul ‘adilah Hayya; Siti Sarah (JOIN: Journal of Indonesian Education and Learning, 2025)
This study explores the Nested Integrated Learning Model as part of the Fogartyapproach and its application in teaching Natural Sciences and Social Studies (IPAS)within the context of the independent curriculum. The primary focus is to analyzethe impact of this model on students' comprehension, utilizing the Classroom ActionResearch (CAR) method across multiple cycles. The research findings indicate thatthe nested integrated learning model positively influences students' understandingof IPAS subjects. The hierarchical and nested approach in delivering the contentprovides a more in-depth understanding. The study also highlights the crucial role ofcollaboration among teachers in effectively implementing this model. This researchcontributes to our understanding of the effectiveness of the Nested Integrated LearningModel, particularly in enhancing students' comprehension of interdisciplinaryconcepts. Practical implications include the potential adoption of this model withinthe independent curriculum at the elementary school level. By strengthening theempirical foundation, this research can serve as a guide for educational practitionersand policymakers in designing a curriculum that is holistic and relevant to students'development in the current educational landscape.